Perancangan Kampanye “Embracing Your Beauty: A Journey Of Self-Love” “Omg” Beauty Class di Cirebon - Angelika Angelika; Ine Rachmawati; Yuni Awalaturrohmah Solihah (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
Research aims to explore the perceptions of women aged 21-38 years old on self-confidence, feelings of insecurity, and self-love through an online survey conducted using Google Forms. The survey results show that 98.4% of respondents experience feelings of insecurity, while 75.8% show interest in attending self-development activities such as beauty classes to enhance self-confidence, and 91.3% show interest in makeup. Interviews were conducted to gain a deeper understanding of the beauty class activities conducted by OMG Beauty in Cirebon, which focus on developing makeup skills and using beauty products, but the interviews also revealed that these activities do not fully reflect OMG Beauty's brand image, which promotes the message "confidence and optimism". Therefore, the researcher proposes a social campaign with the theme "Embracing Your Beauty: A Journey of Self-love" to increase awareness of the importance of nurturing self-confidence and addressing feelings of insecurity among participants. The campaign is designed using the Design Thinking method, which includes the stages of Empathize, Define, Ideate, Prototype, and Test, to create an effective solution for increasing participation and public perception of beauty classes.